24.5k views
5 votes
Solve this system by substitution. y = 6x - 17 y = -4x + 3

Solve this system by substitution. y = 6x - 17 y = -4x + 3-example-1
User Mr Jax
by
4.8k points

1 Answer

4 votes

Answer:

x = 2 y = -5

Explanation:

Notice that both equations are equal to y

Substitute equation 2 into equation 1:


-4x+3=6x-17

Simplify:


-10x=-20

Divide both sides by -10:


x=2

Plug -2 into either equation to solve for y:


y=6(2)-17=-5

User Davie Brown
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.